2013
DOI: 10.28945/1921
|View full text |Cite
|
Sign up to set email alerts
|

Themes of Tension Surrounding Research Methodologies Education in an Accelerated, Cohort-Based Doctoral Program

Abstract: This single-site investigative action research study used an insider research strategy using selfdirected focus groups comprised of the four participants/researchers. These "four voices" include the Program Director of the doctoral program in instruction and leadership, a recent program graduate, and two faculty members who teach the quantitative and qualitative components of the program. Survey data from students represent the "fifth voice". The focus of our research was to discuss the most effective ways to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Teaching research skills to novice researchers is another process underpinning the doctoral journey. Instructors must teach research skills to doctoral students who do not spend a lot of time learning the methodology that they will use in their dissertation (Bernauer, Semich, Klentzin, & Holdan, 2013). Research depicts a disturbing picture of doctoral departure, and implementing technological management systems may improve the doctoral process.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching research skills to novice researchers is another process underpinning the doctoral journey. Instructors must teach research skills to doctoral students who do not spend a lot of time learning the methodology that they will use in their dissertation (Bernauer, Semich, Klentzin, & Holdan, 2013). Research depicts a disturbing picture of doctoral departure, and implementing technological management systems may improve the doctoral process.…”
Section: Discussionmentioning
confidence: 99%
“…Rather they seek to further develop their existing identity as an experienced professional (Kerrigan & Hayes, 2016). Third, the highly structured pace of EdD coursework, which often privileges problemcentered application, does not afford students extended opportunities to explore methodologies prior to developing their dissertation or capstone project (Bernauer, Semich, Klentzin, & Holdan, 2013). This lack of exposure to research is exacerbated in programs where classes are held off campus, because "the development of relationships with other scholars beyond their immediate classroom contact is minimal" (Bernauer et al, 2013, p. 175).…”
Section: How Peer Mentoring Addresses Challenges Doctoral Students Facementioning
confidence: 99%
“…FR introduced the process of Oral Coding in a study that focused on higher education (Bernauer, Semich, Klentzin, & Holdan, 2013) where one of his co-authors used phenomenological coding while FR used Oral Coding to analyze data that were collected during focus group sessions. It was found that there was substantial agreement across findings and interpretations.…”
Section: Framework and Methodsmentioning
confidence: 99%